Positive electrode for lithium-sulfur secondary battery with pattern, method for manufacturing the same, and lithium-sulfur secondary battery comprising the positive electrode

By forming a gravure pattern on the positive electrode of the lithium-sulfur secondary battery and using sulfur-carbon composite materials, the problems of polysulfide dissolution and low porosity in lithium-sulfur secondary batteries are solved, and the energy density and battery performance per unit volume are improved.

CN113812017BActive Publication Date: 2025-01-17LG ENERGY SOLUTION LTD
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
CN202080033916.0
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2019-09-24
Filing Date
2020-09-16
Publication Date
2025-01-17
Estimated Expiration
2040-09-16

AI Technical Summary

Technical Problem

During the charging/discharging process of lithium-sulfur secondary batteries, the dissolution and adsorption of polysulfides affect the performance, and the positive electrode with low porosity leads to the wettability of the electrolyte, limiting the energy density per unit volume.

Method used

By forming a gravure pattern on the positive electrode of the lithium-sulfur secondary battery, adjusting the shape of the positive electrode active material layer, improving the moving characteristics and porosity of the material, using sulfur-carbon composite materials and laser patterning technology to form a porosity of 50% to 65% to increase energy density.

Benefits of technology

The energy density per unit volume is significantly improved, and the discharge capacity of the high porosity positive electrode is maintained, ensuring the improvement of battery performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN113812017B_ABST
    Figure CN113812017B_ABST
Patent Text Reader

Abstract

The present invention provides a positive electrode for a lithium-sulfur secondary battery including a positive electrode active material layer having a gravure pattern formed therein, a method for manufacturing the same, and a lithium-sulfur secondary battery including the same. The positive electrode active material layer has a porosity of 50% to 65%. The gravure pattern has a width of 1 μm to 100 μm and a depth of 30% to 99% based on the thickness of the positive electrode active material layer. The volume ratio of the positive electrode active material layer to the gravure pattern is 4:1 to 40:1. When the positive electrode is applied to a lithium-sulfur secondary battery, the energy density per unit volume can be significantly improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a positive electrode for a lithium-sulfur secondary battery, a method for manufacturing the positive electrode, and a lithium-sulfur secondary battery comprising the positive electrode.

[0002] This application claims the benefit of priority based on Korean Patent Application Nos. 10-2019-0117573 and 10-2019-0117755, filed on September 24, 2019, which are hereby incorporated by reference in their entirety. Background Art

[0003] As the application fields of secondary batteries expand to electric vehicles (EV) or energy storage systems (ESS), the application of lithium-ion secondary batteries with relatively low energy storage density per unit weight (~250Wh / kg) in these products is limited. Alternatively, lithium-sulfur batteries have attracted attention as the next-generation secondary battery technology because they can achieve a theoretically high energy storage density per unit weight (~2,600Wh / kg).

[0004] Lithium-sulfur battery refers to a battery system that uses a sulfur-based material with an SS bond (sulfur-sulfur bond) as a positive electrode active material and lithium metal as a negative electrode active material. The advantage of sulfur as the main material of the positive electrode active material is that it is very abundant in resources, non-toxic and has a low atomic weight.

[0005] In a lithium-sulfur secondary battery, when the battery is discharged, lithium, which is the negative electrode active material, is oxidized while releasing electrons and thereby ionizing, while the sulfur-based material, which is the positive electrode active material, is reduced while receiving electrons. In this case, the oxidation reaction of lithium is a process in which lithium metal releases electrons and is converted into a lithium cation form. In addition, the reduction reaction of sulfur is a process in which the SS bond receives two electrons and is converted into a sulfur anion form. The lithium cations generated by the oxidation reaction of lithium are transferred to the positive electrode through the electrolyte and combined with the sulfur anions generated by the reduction reaction of sulfur to form a salt. Specifically, before discharge, sulfur has a cyclic S8 structure, which is converted into lithium polysulfide (LiS) through a reduction reaction. x ). When lithium polysulfide is completely reduced, lithium sulfide (Li2S) is generated.

[0006] In lithium-sulfur secondary batteries, polysulfides are repeatedly dissolved and adsorbed during the charge / discharge process, so higher molecular weight polysulfides and the movement of lithium ions in the electrolyte have an important impact on the performance of lithium-sulfur secondary batteries. In addition, the electrolyte that dissolves a large amount of polysulfides has high viscosity and slows down the diffusion rate of lithium ions. Because the performance of the battery varies greatly with the mobility characteristics of the material, the related art also introduces a positive electrode containing a large number of internal pores by using porous carbon materials to improve the mobility characteristics of the material.

[0007] However, if the porosity of the positive electrode is increased, the energy density may be increased, but the volume occupied by the pores increases the volume of the positive electrode, resulting in a problem of reduced energy density per unit volume. In order to miniaturize the battery, the related technical field requires a method for increasing the energy density per unit volume.

[0008] On the other hand, in the case of lithium secondary batteries using lithium-based oxides such as LiCoO2, LiMn2O4, LiNiO2, and LiMnO2 as positive electrode active materials, because materials with large molecular weights such as polysulfides do not move, the porosity of the electrode has no significant effect on battery performance. Therefore, in lithium secondary batteries, the positive electrode has a much lower porosity than lithium-sulfur secondary batteries, and the positive electrode with such a low porosity has problems with wettability with the electrolyte at the surface. Patent Publication No. 10-2015-0082958 published by South Korea solves this problem by patterning the positive electrode with a laser, thereby increasing the specific surface area of ​​the positive electrode to improve the wettability problem with the electrolyte on the positive electrode surface. In contrast, because lithium-sulfur secondary batteries contain many pores in the positive electrode, the electrolyte is easily infiltrated, and the wettability between the electrolyte and the positive electrode is not a problem. Therefore, in lithium-sulfur secondary batteries, it is generally not necessary to use the above-mentioned laser patterning technology.

[0009] The inventors of the present invention have recognized that by using laser patterning technology on the positive electrode of a lithium-sulfur secondary battery with low porosity, the shape of the positive electrode active material layer (the shape of the pores) is changed by processing the surface with a specific pattern, thereby increasing the energy density of the lithium-sulfur secondary battery per unit volume without increasing the wettability of the electrolyte and the positive electrode in the lithium-sulfur secondary battery, thereby improving the performance of the battery, thereby completing the present invention.

[0010] [Prior art literature]

[0011] [Patent Document]

[0012] (Patent Document 1) Korean Patent Publication No. 10-2015-0082958 Summary of the invention

[0013] [Technical issues]

[0014] The present invention aims to provide a positive electrode for a lithium-sulfur secondary battery, which can improve the energy density per unit volume of the battery by changing the shape (pore shape) of the positive electrode active material layer to improve the material mobility characteristics in the positive electrode active material layer.

[0015] [Technical solution]

[0016] According to a first aspect of the present invention, the present invention provides a positive electrode for a lithium-sulfur secondary battery, the positive electrode for a lithium-sulfur secondary battery comprising a positive electrode active material layer having a gravure pattern formed therein, wherein the porosity of the positive electrode active material layer is 50% to 65%.

[0017] In one embodiment of the present invention, the width of the gravure pattern is 1 μm to 100 μm.

[0018] In one embodiment of the present invention, the depth of the gravure pattern is 30% to 99% based on the thickness of the positive electrode active material layer.

[0019] In one embodiment of the present invention, the volume ratio of the positive electrode active material layer to the gravure pattern is 4:1 to 40:1.

[0020] In one embodiment of the present invention, the intaglio pattern has a shape of a plurality of straight or dotted lines that are horizontal or perpendicular to each other.

[0021] In one embodiment of the present invention, the intaglio pattern has a shape of a plurality of dots formed in a manner of being spaced apart from each other.

[0022] In one embodiment of the present invention, the intaglio pattern is located within 200 μm based on a predetermined point located on the surface of the positive electrode active material layer.

[0023] In one embodiment of the present invention, the positive electrode active material layer includes 60 to 95 parts by weight of the positive electrode active material based on 100 parts by weight of the positive electrode active material layer.

[0024] In one embodiment of the present invention, the positive electrode active material includes a sulfur-carbon composite material, and the sulfur-carbon composite material contains 60 to 90 parts by weight of sulfur based on 100 parts by weight of the sulfur-carbon composite material.

[0025] According to a second aspect of the present invention, there is provided a method for manufacturing the positive electrode for the above-mentioned lithium-sulfur secondary battery, the method comprising the following steps: (1) forming a positive electrode active material layer before rolling by applying a slurry for forming a positive electrode active material onto a current collector; (2) forming a positive electrode active material layer after rolling by rolling the positive electrode active material layer before rolling; and (3) forming a positive electrode active material layer having a gravure pattern, the gravure pattern being formed by irradiating a laser on the surface of the positive electrode active material layer after rolling, wherein the porosity of the positive electrode active material layer after rolling is 50% to 65%.

[0026] According to a third aspect of the present invention, the present invention provides a lithium-sulfur secondary battery comprising the above-mentioned positive electrode.

[0027] [Beneficial Effects]

[0028] By rolling the positive electrode active material layer to form a positive electrode active material layer having a small number of uniform pores and then patterning the surface of the positive electrode active material layer, the positive electrode for a lithium-sulfur secondary battery according to the present invention can significantly improve the energy density per unit volume when applied to a battery.

[0029] Furthermore, the positive electrode for a lithium-sulfur secondary battery according to the present invention, when applied to a battery, can maintain the same discharge capacity as a battery including a positive electrode active material having a high porosity even if the amount of the positive electrode active material is reduced due to patterning. BRIEF DESCRIPTION OF THE DRAWINGS

[0030] Figures 1a to 1f is an image showing a top view of a positive electrode active material layer having an exemplary gravure pattern shape.

[0031] Figure 2 is an image showing a cross-sectional view of a positive electrode active material layer in which an intaglio pattern is formed.

[0032] Figure 3 is a graph showing the results of thermogravimetric analysis of the positive electrode active material layers according to Examples 1 to 3 before and after patterning.

[0033] Figure 4 is a graph showing charge / discharge curves of battery potential relative to specific capacity obtained by initially charging / discharging the lithium-sulfur secondary batteries according to Example 1 and Comparative Examples 3 and 4 at a 0.1 C rate.

[0034] Figure 5 is a graph showing charge / discharge curves of battery potential relative to specific capacity obtained by initially charging / discharging the lithium-sulfur secondary batteries according to Examples 2 and 3 and Comparative Example 5 at a 0.1 C rate.

[0035] Figure 6 is a graph showing a charge / discharge curve of a battery potential with respect to a specific capacity obtained by initially charging / discharging the lithium-sulfur secondary batteries according to Comparative Examples 1 and 2 at a 0.1 C rate.

[0036] Figure 7 : is a graph showing a charge / discharge curve of a battery potential with respect to a specific capacity obtained by initially charging / discharging the lithium-sulfur secondary batteries according to Example 2 and Comparative Example 6 at a 0.1 C rate.

[0037] Figure 8a and 8b These are images obtained by analyzing the negative electrode surface after the lithium-sulfur secondary batteries according to Example 1 and Comparative Example 6 were charged / discharged 50 times at a rate of 0.1 C.

[0038] Fig. 9 It is a schematic diagram showing a method for manufacturing a positive electrode for a lithium-sulfur secondary battery according to the present invention. DETAILED DESCRIPTION

[0039] The embodiments provided by the present invention can all be realized through the following description. The following description should be understood as describing the preferred embodiments of the present invention, and it should be understood that the present invention is not necessarily limited thereto.

[0040] For the physical properties described herein, if the measurement conditions and methods are not specifically described, the physical properties are measured according to the measurement conditions and methods generally used by those skilled in the art.

[0041] Positive electrode active material layer with pattern

[0042] The present invention provides a positive electrode active material layer in which a gravure pattern is formed as a configuration of a positive electrode for a lithium-sulfur secondary battery. The gravure pattern refers to a pattern in which a portion where the pattern is formed is lower than a peripheral portion. In the present invention, the gravure pattern is formed in the positive electrode active material layer by irradiating a laser to the positive electrode active material layer so that a portion of the positive electrode active material layer disappears.

[0043] The positive electrode active material layer is a coating layer formed on the positive electrode current collector and containing a positive electrode active material. The positive electrode active material layer contains a conductive material and a binder as well as the positive electrode active material.

[0044] The positive electrode active material may be selected from: elemental sulfur (S8), sulfur-carbon composite materials, sulfur-based compounds or mixtures thereof, but is not necessarily limited thereto. Specifically, the sulfur-based compound may be Li2S n (n≥1), organic sulfur compounds or carbon-sulfur composite materials ((C2S x ) n : x = 2.5 to 50, n ≥ 2). These sulfur materials are used in combination with a conductive material because they do not have conductivity alone. In addition, the sulfur-carbon composite material can be an aspect of a positive electrode active material formed by mixing carbon and elemental sulfur or a sulfur-based compound to reduce the dissolution of sulfur into an electrolyte and improve the conductivity of a sulfur-containing electrode. The proportion of the positive electrode active material in the positive electrode active material layer can be adjusted in consideration of the performance of the target battery. According to one embodiment of the present invention, the positive electrode active material layer contains 60 to 95 parts by weight of the positive electrode active material based on 100 parts by weight of the positive electrode active material layer.

[0045] The carbon material constituting the sulfur-carbon composite material may be crystalline carbon or amorphous carbon, and may be conductive carbon. Specifically, the carbon material may be selected from the group consisting of graphite, graphene, Super P, carbon black, deco black, acetylene black, Ketjen black, channel black, furnace black, lamp black, thermal black, carbon fiber, carbon nanofiber, carbon nanotube, carbon nanowire, carbon nanoring, carbon fabric, and fullerene (C60).

[0046] Exemplary sulfur-carbon composite materials are sulfur-carbon nanotube composite materials and the like. Specifically, the sulfur-carbon nanotube composite material contains sulfur or sulfur compounds in the carbon nanotube aggregate having a three-dimensional structure and in at least a portion of the inner surface and outer surface of the carbon nanotube aggregate. Because the sulfur-carbon nanotube composite material according to one embodiment of the present invention contains sulfur present inside the three-dimensional structure of the carbon nanotube, if the soluble polysulfide can be located inside the carbon nanotube even if the soluble polysulfide is produced due to the electrochemical reaction, the collapse of the positive electrode structure can be suppressed by maintaining the three-dimensional entangled structure even when the polysulfide is dissolved. As a result, the lithium-sulfur secondary battery containing the sulfur-carbon nanotube composite material has the advantage of being able to achieve high capacity even under high load. In addition, sulfur or sulfur-based compounds may be contained in the inner pores of the carbon nanotube aggregate. Carbon nanotube refers to linear conductive carbon, and specifically, the carbon nanotube may be a carbon nanotube (CNT), a graphite nanofiber (GNF), a carbon nanofiber (CNF) or an activated carbon fiber (ACF). Both single-walled carbon nanotubes (SWCNTs) and multi-walled carbon nanotubes (MWCNTs) can be used.

[0047] According to one embodiment of the present invention, the sulfur-carbon composite material is prepared by impregnating sulfur or a sulfur-based compound on the outer surface and inside of the carbon, and a step of adjusting the diameter of the carbon may be optionally performed before, after, or before and after the impregnation step. The impregnation step may be performed by mixing the carbon with a powder of sulfur or a sulfur-based compound, and then heating to impregnate the carbon with molten sulfur or a sulfur-based compound, and this mixing can be performed by a dry ball milling method, a dry jet milling method, or a dry Dyno-mill method. According to one embodiment of the present invention, based on 100 parts by weight of the sulfur-carbon composite material, the sulfur-carbon composite material contains 60 to 90 parts by weight of sulfur or a sulfur-based compound. When the content of sulfur or a sulfur-based compound in the sulfur-carbon composite material is adjusted within the above range, while the content of the sulfur or sulfur-based compound is maintained at a high ratio, electrons are appropriately supplied to the non-conductive sulfur or sulfur-based compound. The sulfur-carbon composite material has a porosity exceeding a specific level because it has a form in which sulfur or a sulfur-based compound is loaded on porous carbon. Therefore, even if the positive electrode active material layer is rolled sufficiently to the extent that the structure of the sulfur-carbon composite material is maintained, the impregnation performance of the electrolyte in the positive electrode active material layer does not deteriorate.

[0048] The conductive material may be selected from: graphite such as natural graphite or artificial graphite; carbon black materials such as carbon black, acetylene black, Ketjen black, channel black, furnace black, lamp black or thermal black; conductive fibers such as carbon fibers or metal fibers; fluorocarbons; metal powders such as aluminum or nickel powders; conductive whiskers such as zinc oxide and potassium titanate; conductive metal oxides such as titanium oxide; or polyphenylene derivatives, but are not necessarily limited thereto. The proportion of the conductive material in the positive electrode active material layer may be adjusted in consideration of the performance of the target battery. According to one embodiment of the present invention, the positive electrode active material layer contains 0.05 to 20 parts by weight of a conductive material based on 100 parts by weight of the positive electrode active material layer.

[0049] The binder is a component that helps the positive electrode active material to bind to the conductive material and to the current collector, and is not particularly limited. For example, the binder can be selected from at least one of the following or a mixture of two or more thereof: vinylidene fluoride-hexafluoropropylene copolymer (PVDF-co-HFP), polyvinylidene fluoride, polyacrylonitrile, polymethyl methacrylate, polyvinyl alcohol, carboxymethyl cellulose (CMC), starch, hydroxypropyl cellulose, regenerated cellulose, polyvinyl pyrrolidone, polytetrafluoroethylene, polyethylene, polypropylene, polyacrylic acid, ethylene propylene diene rubber (EPDM), sulfonated EPDM, styrene butadiene rubber (SBR) and fluororubber. According to one embodiment of the present invention, based on 100 parts by weight of the positive electrode active material layer, the positive electrode active material layer contains 1 to 30 parts by weight of the binder.

[0050] The positive electrode active material layer has an intaglio pattern on the surface. The intaglio pattern is formed by irradiating the surface of the positive electrode active material layer with laser. The specific manufacturing method will be described later.

[0051] Because the positive electrode active material layer can ensure pores of the desired shape by the gravure pattern, it is preferred that the positive electrode active material layer has a low porosity before the gravure pattern is formed. Here, the porosity is the ratio of the pore volume to the total volume of the positive electrode active material layer, and is generally expressed as a percentage. In this specification, when calculating the porosity of the positive electrode active material layer, it is considered that the shape of the positive electrode active material layer itself is changed by patterning, so that the pores artificially formed by patterning are not included in the total volume and pore volume of the positive electrode active material layer. Therefore, the positive electrode active material layer maintains the same porosity before and after patterning. According to one embodiment of the present invention, the porosity of the positive electrode active material layer is less than 70%, preferably 50% to 65%, and more preferably 55% to 62%. In general lithium-sulfur secondary batteries, it is undesirable to keep the porosity below 70% because the material movement caused by electrolyte penetration may not be easy. However, in the lithium-sulfur secondary battery according to the present invention, because the channel for material movement can be ensured by patterning, the performance of the battery will not be significantly deteriorated even under low porosity conditions. Because the porosity of the sulfur-carbon composite material mainly used as a positive electrode active material in a lithium-sulfur secondary battery exceeds a specific level, a positive electrode active material layer having a porosity of less than 70% is prepared by coating a slurry for forming a positive electrode active material layer on a positive electrode current collector and then rolling them, and the porosity of the positive electrode active material layer is not lower than the porosity of the sulfur-carbon composite material even when rolling. When the entire coated slurry for forming a positive electrode active material layer is rolled at the same pressure, the porosity inside the positive electrode active material layer can be uniformly maintained. In addition, as described above, since patterning does not affect the porosity of the positive electrode active material layer, the porosity of the positive electrode active material is uniformly maintained even after patterning.

[0052] The intaglio pattern can be made into various shapes and sizes. According to one embodiment of the present invention, the intaglio pattern may have a shape of a plurality of straight lines or dotted lines that are horizontal or vertical to each other, or may have a shape of a plurality of dots that are formed in a manner spaced apart from each other. The shape of an exemplary intaglio pattern suitable for the present invention is shown in Figures 1a to 1fIn order to improve the performance of material movement by forming a gravure pattern on the positive electrode active material layer, it is important to arrange the shape of the gravure pattern at regular intervals. According to one embodiment of the present invention, it is expected that the gravure pattern is located within 200 μm, preferably within 175 μm, and more preferably within 150 μm based on a predetermined point on the surface of the positive electrode active material layer. Here, the description that the gravure pattern is located within 200 μm based on the predetermined point means that the straight-line distance to the nearest gravure pattern at any point on the surface of the positive electrode active material layer is less than 200 μm. If the gravure pattern based on the predetermined point on the surface of the positive electrode active material layer exceeds 200 μm, the electrochemical reaction will proceed unevenly around this point during the battery charge / discharge process, and the result can be confirmed by the concave-convex on the surface of the negative electrode facing it after multiple cycles.

[0053] In addition to the shape of the gravure pattern, the size of the gravure pattern also plays an important role in improving the performance of the battery. The size of the gravure pattern may be determined in consideration of factors such as width, depth, and volume of the gravure pattern. Figure 2It is an image showing a cross-sectional view of a positive electrode active material layer in which a gravure pattern is formed. As shown in the figure above, the width of the gravure pattern refers to the length of the gravure pattern in a direction parallel to the surface of the positive electrode active material layer, and the depth of the gravure pattern refers to the length of the gravure pattern in a direction perpendicular to the surface of the positive electrode active material layer. In a specific shape, if the shape of the gravure pattern is a straight line or a dotted line based on the surface of the positive electrode active material layer, the width of the gravure pattern refers to the thickness of the line, and if the shape of the gravure pattern is a point, the width of the gravure pattern refers to the diameter of the point. According to one embodiment of the present invention, the width of the gravure pattern may be 1 to 100 μm, preferably 30 to 100 μm, and more preferably 60 to 100 μm. If the width of the gravure pattern is less than 1 μm, it is not preferred because the mobility of materials with large molecular weights such as polysulfides formed during electrochemical reactions is not good. If the width of the gravure pattern exceeds 100 μm, when the gravure pattern is arranged considering the spacing, the overall volume of the gravure pattern is large, so there is a problem that the positive electrode active material cannot be highly loaded. According to one embodiment of the present invention, the depth of the gravure pattern may be 30% to 99%, preferably 50% to 97%, and more preferably 70% to 95%, based on the thickness of the positive active material layer. If the depth of the gravure pattern is less than 30% based on the thickness of the positive active material layer, the effect of improving battery performance may be reduced because the material at the deep point in the positive active material layer close to the positive current collector is not easy to move. In the case of forming a pattern with a roller having concave and convex, the width of the gravure pattern cannot be reduced to form a micro unit, and if a high pressure is applied to deeply form the gravure pattern, there is a risk that the basic structure of the positive active material may be damaged. According to one embodiment of the present invention, the volume ratio of the positive active material layer to the gravure pattern may be 4: 1 to 40: 1, preferably 4: 1 to 20: 1, and more preferably 4: 1 to 10: 1. If a plurality of gravure patterns are formed separately on the positive active material layer, the volume ratio is calculated based on the total volume of the gravure pattern. If the ratio of the positive active material layer is less than 4: 1, it is undesirable because the positive active material cannot be highly loaded. If the ratio of the positive electrode active material layer exceeds 40:1, it is not preferable because the effect of improving battery performance by patterning is not significant.

[0054] Method for manufacturing positive electrode active material layer having pattern formed therein

[0055] The present invention provides a method for manufacturing a positive electrode for a lithium-sulfur secondary battery, the method comprising the following steps: (1) forming a positive electrode active material layer before rolling by applying a slurry for forming a positive electrode active material onto a current collector; (2) forming a positive electrode active material layer after rolling by rolling the positive electrode active material layer before rolling; and (3) forming a positive electrode active material layer having a gravure pattern, the gravure pattern being formed by irradiating a laser on the surface of the positive electrode active material layer after rolling, wherein the porosity of the positive electrode active material layer after rolling is 50% to 65%. Fig. 9 A method for producing a positive electrode for a lithium-sulfur secondary battery is shown.

[0056] According to one embodiment of the present invention, a method for manufacturing a positive electrode for a lithium-sulfur secondary battery may include the following steps: (1) forming a positive electrode active material layer before rolling by applying a slurry for forming a positive electrode active material onto a current collector.

[0057] The porosity of the positive electrode active material layer before rolling in step (1) can be 60% to 80%, preferably 60% to 75%, and more preferably 64% to 73%. If the porosity of the positive electrode active material layer before rolling is less than the above range, there is a problem that it cannot be fully rolled in the rolling step, and even if it can be rolled, the impregnation performance of the electrolyte in the positive electrode active material layer may deteriorate. If the porosity of the positive electrode active material layer before rolling exceeds the above range, the porosity is high even after rolling, and it is difficult to obtain the effect of improving the performance of the battery of the present invention. Therefore, it is preferred to meet the above range.

[0058] In addition, the slurry for forming the positive electrode active material in step (1) may include a positive electrode active material, a conductive material, and a binder. The composition of the slurry for forming the positive electrode active material is as described above.

[0059] According to one embodiment of the present invention, a method for manufacturing a positive electrode for a lithium-sulfur secondary battery may include the following steps: (2) forming a positive electrode active material layer after rolling by rolling the positive electrode active material layer before rolling.

[0060] The porosity of the positive electrode active material layer after rolling can be less than 70%, preferably 50-65%, and more preferably 55%-62%. If the porosity of the positive electrode active material after rolling is less than the above range, there is a problem that it is difficult to exert sufficient discharge capacity when applied to a lithium-sulfur secondary battery. If the porosity of the positive electrode active material after rolling exceeds the above range, there is a problem that the energy density per unit volume is reduced when applied to a lithium-sulfur secondary battery. Therefore, it is preferred that the porosity of the positive electrode active material after rolling satisfies the above range. In general lithium-sulfur secondary batteries, it is undesirable if the porosity is kept below 70% because the material may not be easy to move due to the penetration of the electrolyte. However, in the lithium-sulfur secondary battery according to the present invention, because the channel for the movement of the material can be ensured by forming a gravure pattern, the performance of the battery will not be significantly deteriorated even under conditions of low porosity. Since the porosity of the sulfur-carbon composite material mainly used as a positive electrode active material in a lithium-sulfur secondary battery exceeds a specific level, a positive electrode active material layer having a porosity of less than 70% is prepared by coating a slurry for forming a positive electrode active material layer on a positive electrode current collector and then rolling the same. Since the entire positive electrode active material layer can be rolled at the same pressure by rolling in step (2), the porosity inside the positive electrode active material layer can be uniformly maintained.

[0061] On the other hand, as described above, since the formation of the pattern does not affect the porosity of the positive electrode active material layer, the porosity of the positive electrode active material layer is uniformly maintained even after the pattern is formed.

[0062] In addition, the rolling in step (2) can be performed by a rolling process. The rolling process can be performed by passing the current collector on which the positive electrode active material layer before rolling is formed through a pair of rollers. Through the rolling process, the entire manufacturing process of the positive electrode for the lithium-sulfur secondary battery can be carried out continuously. In addition, the pressure applied during the rolling process can be 300 to 1000KgF. When the pressure applied during the rolling process is adjusted within the above range, the porosity of the positive electrode active material layer can be reduced by fully rolling the positive electrode active material layer without destroying the positive electrode active material layer after rolling. In addition, the energy density per unit volume can be increased thereby.

[0063] In addition, relative to the thickness of the positive electrode active material layer before rolling in step (1), the thickness of the positive electrode active material layer after rolling in step (2) can be 80% to 99%, preferably 85% to 96%, and more preferably 85.9% to 95.8%. If the thickness of the positive electrode active material layer after rolling is less than the above range, the positive electrode active material layer may be crushed. If the thickness of the positive electrode active material layer after rolling exceeds the above range, the rolling of the positive electrode active material layer is insufficient, so that the energy density per unit volume cannot be fully increased. Therefore, it is preferred that the thickness of the positive electrode active material layer after rolling meets the above range.

[0064] According to one embodiment of the present invention, the method for manufacturing a positive electrode for a lithium-sulfur secondary battery may include the following steps: (3) forming a positive electrode active material layer having a gravure pattern, wherein the gravure pattern is formed by irradiating a laser on the surface of the rolled positive electrode active material layer.

[0065] The wavelength of the laser irradiated in step (3) may be in the range of 300 to 2000 nm, and the frequency thereof may be in the range of 10 to 1000 kHz.

[0066] In addition, the load loss rate of the positive electrode active material layer through step (3) can be less than 30%, preferably 5% to 20%, and more preferably 10% to 20%. The load loss rate represents the volume of the positive electrode active material layer removed by forming a gravure pattern relative to the volume of the entire positive electrode active material layer after rolling. If multiple gravure patterns are formed separately on the positive electrode active material layer, the volume ratio is calculated based on the total volume of the gravure patterns. If the load loss rate of the positive electrode active material layer is less than the above range, the effect of improving the battery performance by forming a gravure pattern is not significant. If the load loss rate of the positive electrode active material layer exceeds the above range, the discharge capacity of the lithium-sulfur secondary battery is insufficient because the positive electrode active material cannot be fully loaded into the positive electrode active material layer. Therefore, it is preferred that the load loss rate satisfies the above range.

[0067] In addition, the intaglio pattern formed by step (3) can be made into various shapes and sizes. These shapes and sizes are as described above.

[0068] Lithium-sulfur secondary battery

[0069] The present invention provides a lithium-sulfur secondary battery having improved performance by forming a positive electrode active material layer having the above pattern on a current collector to prepare a positive electrode, and then adding a negative electrode, a separator, and an electrolyte.

[0070] The positive electrode constituting the lithium-sulfur secondary battery according to the present invention comprises a positive electrode collector and a positive electrode active material layer formed on the positive electrode collector. The positive electrode active material layer is manufactured by final patterning according to the above description. There is no particular limitation on the positive electrode collector as long as it is generally used to prepare the positive electrode. According to one embodiment of the present invention, the positive electrode collector may be at least one material selected from the following: stainless steel, aluminum, nickel, titanium and sintered carbon, and if necessary, the surface of the above material may be treated with carbon, nickel, titanium or silver. According to one embodiment of the present invention, the shape of the positive electrode collector may be selected from a film, a sheet, a foil, a mesh, a porous body, a foam and a non-woven fabric. There is no particular limitation on the thickness of the positive electrode collector, and it may be set within a suitable range in consideration of the mechanical strength of the positive electrode, the productivity, the capacity of the battery, etc.

[0071] The method for forming the positive electrode active material layer on the positive electrode current collector may be a known coating method and is not particularly limited. For example, the coating method may be a rod coating method, a screen coating method, a doctor blade method, a dipping method, a reverse roller method, a direct roller method, a gravure printing method, or an extrusion method. There is no particular restriction on the amount of the positive electrode active material layer coated on the positive electrode current collector, and the thickness of the positive electrode active material layer is adjusted in consideration of the final desired thickness. In addition, before or after the process of forming the positive electrode active material layer, a known process required for preparing the positive electrode, such as a rolling or drying process, may be performed.

[0072] There is no particular restriction on the electrolyte constituting the lithium-sulfur secondary battery according to the present invention, as long as it is a non-aqueous solvent that acts as a medium through which ions participating in the electrochemical reaction of the battery can move. According to one embodiment of the present invention, the solvent may be a carbonate solvent, an ester solvent, an ether solvent, a ketone solvent, an alcohol solvent or an aprotic solvent. Examples of carbonate solvents may specifically include dimethyl carbonate (DMC), diethyl carbonate (DEC), dipropyl carbonate (DPC), methyl propyl carbonate (MPC), ethyl propyl carbonate (EPC), ethyl methyl carbonate (MEC), ethylene carbonate (EC), propylene carbonate (PC) or butylene carbonate (BC), etc. Examples of ester solvents may specifically include methyl acetate, ethyl acetate, n-propyl acetate, 1,1-dimethylethyl acetate, methyl propionate, ethyl propionate, γ-butyrolactone, decanolactone, valerolactone, mevalonolactone or caprolactone, etc. Examples of ether solvents may specifically include diethyl ether, dipropyl ether, dibutyl ether, dimethoxymethane, trimethoxymethane, dimethoxyethane, diethoxyethane, diethylene glycol dimethyl ether, triethylene glycol dimethyl ether, tetraethylene glycol dimethyl ether, tetrahydrofuran, 2-methyltetrahydrofuran or polyethylene glycol dimethyl ether, etc. Examples of ketone solvents may specifically include cyclohexanone, etc. Examples of alcohol solvents may specifically include ethanol or isopropanol, etc. Examples of aprotic solvents may specifically include: nitrile substances such as acetonitrile; amide substances such as dimethylformamide; dioxolane substances such as 1,3-dioxolane (DOL), or cyclopentane sulfone, etc. The non-aqueous organic solvent may be used alone or in one or more combinations. The mixing ratio when used in one or more combinations can be appropriately adjusted according to the desired battery performance. In particular, a mixture of 1,3-dioxolane and dimethoxyethane in a volume ratio of 1:1 may be preferred.

[0073] The negative electrode constituting the lithium-sulfur secondary battery according to the present invention includes a negative electrode current collector and a negative electrode active material layer formed on the negative electrode current collector.

[0074] The negative electrode active material layer includes a negative electrode active material, a binder and a conductive material. The negative electrode active material can be a material that can reversibly insert or remove lithium ions (Li + ), a material capable of reacting with lithium ions to reversibly form a lithium-containing compound, lithium metal or a lithium alloy. + ) can be, for example, crystalline carbon, amorphous carbon or a mixture thereof. +) to reversibly form a lithium-containing compound may be, for example, tin oxide, titanium nitrate, or silicon. The lithium alloy may be, for example, an alloy of lithium (Li) and a metal selected from the group consisting of sodium (Na), potassium (K), rubidium (Rb), cesium (Cs), francium (Fr), beryllium (Be), magnesium (Mg), calcium (Ca), strontium (Sr), barium (Ba), radium (Ra), aluminum (Al), and tin (Sn).

[0075] The binder, conductive material and negative electrode current collector can be selected with reference to the configuration in the above positive electrode, but are not necessarily limited thereto. In addition, the method of forming the negative electrode active material layer on the negative electrode current collector is performed by a known coating method as in the positive electrode, and is not particularly limited.

[0076] The separator for lithium-sulfur secondary batteries according to the present invention is a physical separator having the function of physically separating electrodes. The separator can be used without particular limitation as long as it is used as a conventional separator. In particular, a separator having excellent moisture retention ability for the electrolyte while exhibiting low resistance to ion migration of the electrolyte is preferred. The separator enables lithium ions to be transmitted between the positive electrode and the negative electrode while separating or insulating the positive electrode and the negative electrode from each other. Such a separator can be made of a porous, non-conductive or insulating material having a porosity of 30 to 50%. Specifically, a porous polymer film can be used, for example, a porous polymer film made of a polyolefin polymer such as an ethylene homopolymer, a propylene homopolymer, an ethylene / butene copolymer, an ethylene / hexene copolymer, and an ethylene / methacrylate copolymer, and a non-woven fabric made of a high melting point glass fiber, etc. can be used. Among them, a porous polymer film is preferably used.

[0077] If a polymer film is used as both a buffer layer and a separator, the amount of electrolyte impregnation and ion conductivity decrease, and the effects of reducing overvoltage and improving capacity characteristics become less obvious. On the contrary, if a non-woven fabric material is used as both a buffer layer and a separator, mechanical hardness cannot be ensured, resulting in a battery short circuit problem. However, if a film-type separator and a polymer non-woven fabric buffer layer are used together, mechanical strength can be ensured while the effect of improving battery performance is obtained due to the use of a buffer layer.

[0078] According to a preferred embodiment of the present invention, an ethylene homopolymer (polyethylene) polymer film is used as a separator, and a polyimide nonwoven fabric is used as a buffer layer. In this case, the polyethylene polymer film preferably has a thickness of 10 μm to 25 μm and a porosity of 40% to 50%.

[0079] The lithium-sulfur secondary battery of the present invention can be manufactured by placing a separator between the positive electrode and the negative electrode to form an electrode assembly and inserting the electrode assembly into a cylindrical battery case or a rectangular parallelepiped battery case, and then injecting an electrolyte. Alternatively, the lithium-sulfur secondary battery of the present invention can be manufactured by laminating the electrode assembly, impregnating the electrode assembly with an electrolyte, and placing the obtained product in a battery case and sealing it.

[0080] Preferred Implementation

[0081] Hereinafter, preferred embodiments are described to help understand the present invention. However, the following examples are provided to help understand the present invention, but the present invention is not limited thereto.

[0082] Example

[0083] Example 1

[0084] Sulfur and carbon nanotubes (CNANO company, MWCNT) were mixed in a weight ratio of 75:25 to prepare a sulfur-carbon composite material as a positive electrode active material. A slurry containing the sulfur-carbon composite material (positive electrode active material), Deco Black (conductive material) and polyacrylic acid (binder, Sigma Aldrich company, Mv~450k) in a weight ratio of 88:5:7 was coated on an aluminum foil so that the loading per unit area was 5.5 mAh / cm 2 , and dried to prepare the positive electrode active material layer before rolling. At this time, the porosity of the positive electrode active material layer before rolling is 75%. Thereafter, a rolling process is used to make the positive electrode active material layer after rolling by applying a pressure of 500KgF to the positive electrode active material layer to pass the electrode through the roller, while narrowing the gap between the rollers until the porosity of the positive electrode active material layer becomes 62%. Here, the porosity of the positive electrode active material layer is calculated by measuring the thickness of the positive electrode active material layer using a material thickness measuring device (TESA, u-hite), and then using the true density of the positive electrode active material layer measured by a device for measuring the true density of the material (Microtrac, BEL Pycno). Here, the loading amount is calculated by calculating the loading amount per 1cm 2 The discharge capacity per electrode area was obtained by assuming that the discharge capacity of 1 g of sulfur in the positive electrode active material layer formed on the current collector was 1200 mAh / g.

[0085] Thereafter, the rolled positive electrode active material layer was linearly patterned with a laser (wavelength: 1064nm, output: 20W, frequency: 20-80kHz, scanning speed: 1000-2000cm / s) at a spacing of 400μm, so that the load loss rate was 10%, thereby manufacturing a positive electrode active material layer with a pattern. Based on the thickness of the positive electrode active material layer, the gravure pattern formed by the laser has a width of 80μm and a depth of 60%. In addition, the volume ratio of the positive electrode active material layer to the gravure pattern is 9:1.

[0086] The positive electrode prepared by the above method was arranged in a manner facing the negative electrode, which was a lithium foil having a thickness of 45 μm, and then a polyethylene separator having a thickness of 20 μm and a porosity of 45% was inserted between the positive electrode and the negative electrode. Thereafter, they were placed in a coin battery case, and an electrolyte in which 1,3-dioxolane and dimethoxyethane were mixed at a weight ratio of 1:1 was injected to manufacture a lithium-sulfur secondary battery.

[0087] Example 2

[0088] A lithium-sulfur secondary battery was manufactured in the same manner as in Example 1, except that roll pressing was performed until the porosity of the positive electrode active material layer became 60%.

[0089] Example 3

[0090] A lithium-sulfur secondary battery was manufactured in the same manner as in Example 1, except that rolling was performed until the porosity of the positive electrode active material layer became 55%, and the load loss rate was adjusted to 20% when the pattern was formed, and after the pattern was formed, the width of the gravure pattern was adjusted to 100 μm, the depth of the gravure pattern was adjusted to 95%, and the volume ratio of the positive electrode active material layer to the gravure pattern was adjusted to 4:1. Considering the load amount lost due to pattern formation in Examples 2 and 3, the load amount per unit volume in Examples 2 and 3 is substantially the same. The unit volume is based on the volume of the positive electrode active material layer before pattern formation.

[0091] Comparative Example 1

[0092] A lithium-sulfur secondary battery was manufactured in the same manner as in Example 1, except that roll pressing was performed until the porosity of the positive electrode active material layer reached 70%.

[0093] Comparative Example 2

[0094] A lithium-sulfur secondary battery was manufactured in the same manner as in Example 1, except that the porosity of the positive electrode active material layer was adjusted to 73% and then rolling and patterning were not performed. Considering the loading amount lost due to patterning in Comparative Example 1, the loading amounts per unit volume of Comparative Examples 1 and 2 were substantially the same.

[0095] Comparative Example 3

[0096] A lithium-sulfur secondary battery was manufactured in the same manner as in Example 1, except that the porosity of the positive electrode active material layer was adjusted to 69%, and then roll pressing and pattern formation were not performed.

[0097] Comparative Example 4

[0098] A lithium-sulfur secondary battery was manufactured in the same manner as in Example 1, except that the porosity of the positive electrode active material layer was adjusted to 66% and then rolling and patterning were not performed. Considering the loading amount lost due to patterning in Example 2, the loading amounts per unit volume of Example 1 and Comparative Example 4 were substantially the same.

[0099] Comparative Example 5

[0100] A lithium-sulfur secondary battery was manufactured in the same manner as in Example 1, except that the porosity of the positive electrode active material layer was adjusted to 64% and then rolling and patterning were not performed. Considering the loading amount lost due to patterning in Examples 2 and 3, the loading amounts per unit volume of Examples 2 and 3 and Comparative Example 5 were substantially the same.

[0101] Comparative Example 6

[0102] A lithium-sulfur secondary battery was manufactured in the same manner as in Example 1, except that the porosity of the positive electrode active material layer was adjusted to 60%, and then roll pressing and pattern formation were not performed.

[0103] Comparative Example 7

[0104] A lithium-sulfur secondary battery was manufactured in the same manner as in Example 1, except that line patterning having the same width and depth as in Example 1 was performed at a pitch of 500 μm.

[0105] Experimental example

[0106] Experimental Example 1: Thermogravimetric Analysis (TGA)

[0107] For Examples 1 to 3, the mass of the positive electrode active material layer before and after pattern formation was measured using a thermogravimetric analyzer (TGA) while the temperature was raised from room temperature to 900° C. in an atmospheric atmosphere at a rate of 10° C. per minute, and the results are shown in Figure 3 middle.

[0108] according to Figure 3 The content of sulfur in the positive electrode active material layer in each example was the same 66 wt %, and these results indicate that sulfur was not volatilized by the laser patterning process.

[0109] Experimental Example 2-1: Initial discharge curve of lithium-sulfur secondary battery

[0110] The lithium-sulfur secondary batteries according to Example 1 and Comparative Examples 3 and 4 were initially charged / discharged at a rate of 0.1C, and the charge / discharge curves of the battery potential relative to the specific capacity are shown in FIG. Figure 4 middle.

[0111] according to Figure 4 It was confirmed that, in the case of the lithium-sulfur secondary battery according to Example 1, a discharge curve was formed having a higher battery potential than that of the lithium-sulfur secondary battery according to Comparative Example 4, and the battery potential was at the same level as that of the lithium-sulfur secondary battery according to Comparative Example 3 having a larger porosity. In the case of the lithium-sulfur secondary battery according to Example 1, although the amount of positive electrode active material loaded per unit volume was substantially the same as that of the lithium-sulfur secondary battery according to Comparative Example 4, and the thickness of the positive electrode active material layer was thinner than that of the lithium-sulfur secondary battery according to Comparative Example 4, because the lithium-sulfur secondary battery according to Example 1 showed a higher energy density than that of the lithium-sulfur secondary battery according to Comparative Example 4, the lithium-sulfur secondary battery according to Example 1 showed a much higher energy density per unit volume than that of the lithium-sulfur secondary battery according to Comparative Example 4. Furthermore, it can be seen that, although the lithium-sulfur secondary battery according to Example 1 has a larger positive electrode active material loading per unit volume and a much thinner thickness of the positive electrode active material layer than the lithium-sulfur secondary battery according to Comparative Example 3, because the lithium-sulfur secondary battery according to Example 1 shows the same level of energy density, the lithium-sulfur secondary battery according to Example 1 has a much higher energy density per unit volume than the lithium-sulfur secondary battery according to Comparative Example 3. An increase in energy density per unit volume means that battery performance is improved.

[0112] Experimental Example 2-2: Initial discharge curve of lithium-sulfur secondary battery

[0113] The lithium-sulfur secondary batteries according to Examples 2 and 3 and Comparative Example 5 were initially charged / discharged at a rate of 0.1C, and the charge / discharge curves of the battery potential relative to the specific capacity are shown in FIG. Figure 5 middle.

[0114] according to Figure 5, it was confirmed that, in the case of the lithium-sulfur secondary batteries according to Examples 2 and 3, a discharge curve having a higher battery potential than that of the lithium-sulfur secondary battery according to Comparative Example 5 was formed. It can be seen that, in the case of the lithium-sulfur secondary batteries according to Examples 2 and 3, although the amount of positive electrode active material loaded per unit volume was substantially the same as that of the lithium-sulfur secondary battery according to Comparative Example 5 and the thickness of the positive electrode active material layer was thinner than that of the lithium-sulfur secondary battery according to Comparative Example 5, because the lithium-sulfur secondary batteries according to Examples 2 and 3 showed a higher energy density than that of the lithium-sulfur secondary battery according to Comparative Example 5, the lithium-sulfur secondary batteries according to Examples 2 and 3 showed a much higher energy density per unit volume than that of the lithium-sulfur secondary battery according to Comparative Example 5. In particular, although the lithium-sulfur secondary battery according to Example 3 had a very low porosity of 55% in the positive electrode active material layer, the lithium-sulfur secondary battery according to Example 3 could have the same level of performance as a battery including a positive electrode active material layer having a high porosity.

[0115] Experimental Example 2-3: Initial discharge curve of lithium-sulfur secondary battery

[0116] The lithium-sulfur secondary batteries according to Comparative Examples 1 and 2 were initially charged / discharged at a rate of 0.1C, and the charge / discharge curves of the battery potential relative to the specific capacity are shown in FIG. Figure 6 middle.

[0117] according to Figure 6 It was confirmed that, in the case of the lithium-sulfur secondary battery according to Comparative Example 1, a discharge curve having a battery potential similar to that of the lithium-sulfur secondary battery according to Comparative Example 2 was formed. The lithium-sulfur secondary battery according to Comparative Example 1 had substantially the same positive electrode active material loading per unit volume as the lithium-sulfur secondary battery according to Comparative Example 2, and had a thinner positive electrode active material layer thickness than the lithium-sulfur secondary battery according to Comparative Example 2, and because the lithium-sulfur secondary battery according to Comparative Example 1 exhibited an energy density similar to that of the lithium-sulfur secondary battery according to Comparative Example 2, the lithium-sulfur secondary battery according to Comparative Example 1 did not have a significantly higher energy density per unit volume than the lithium-sulfur secondary battery according to Comparative Example 2.

[0118] Experimental Example 2-4: Initial discharge curve of lithium-sulfur secondary battery

[0119] The lithium-sulfur secondary batteries according to Example 2 and Comparative Example 6 were initially charged / discharged at a rate of 0.1C, and the charge / discharge curves of the battery potential relative to the specific capacity are shown in FIG. Figure 7 middle.

[0120] according to Figure 7, it was confirmed that, even when the porosity of the positive electrode active material layer was the same, the lithium-sulfur secondary battery with the formed pattern (Example 2) exhibited superior performance in terms of energy density and specific discharge capacity than the lithium-sulfur secondary battery without the pattern (Comparative Example 6).

[0121] Experimental Example 3: Surface Analysis of Negative Electrode

[0122] The lithium-sulfur secondary batteries according to Example 1 and Comparative Example 6 were charged / discharged at a rate of 0.1C for 50 cycles, and then the negative electrode surfaces were analyzed using a laser profiler. The results are shown in Figure 8a (Example 1) and 8b (Comparative Example 6).

[0123] according to Figure 8a and 8b , if the spacing between the gravure patterns is 500 μm, the midpoint between the gravure patterns on the surface of the positive electrode active material layer where the gravure pattern is not formed is 210 μm away from the gravure pattern at most, making it difficult for the gravure pattern to disperse the electrochemical reaction, thereby rapidly consuming the negative electrode active material facing the corresponding point, causing the surface of the negative electrode to be uneven, such as the negative electrode current collector being exposed ( Figure 8b ). In contrast, if the spacing between the gravure patterns is 400 μm, the distance between the midpoint between the gravure patterns on the surface of the positive electrode active material layer where the gravure patterns are not formed is close to 160 μm, thereby effectively dispersing the electrochemical reaction by the gravure patterns, thereby eliminating problems such as exposure of the negative electrode current collector ( Figure 8a ).

[0124] As described above, in order to eliminate the unevenness of the electrochemical reaction caused by forming the gravure pattern, the pattern forming operation should be finely performed in such a manner that the spacing between the gravure patterns is less than 500 μm, and it is difficult to achieve such a fine pattern using a roll patterning method other than the laser patterning method. In addition, the roll patterning method causes the positive electrode active material layer to be rolled unevenly according to the concave-convex shape of the roll, so that the porosity of the positive electrode active material layer after patterning cannot be uniformly maintained.

[0125] All simple modifications or changes to the present invention belong to the protection scope of the present invention, and the specific protection scope of the present invention shall be subject to the claims.

Claims

1. A positive electrode for a lithium-sulfur secondary battery, comprising a positive electrode active material layer having a gravure pattern formed therein, wherein the positive electrode active material layer has a porosity of 50% to 65%, and a volume ratio of the positive electrode active material layer to the gravure pattern is 4:1 to 40:1, The spacing between the gravure patterns is less than 500 μm, The intaglio pattern is formed by irradiating a positive electrode active material layer with laser to remove a portion of the positive electrode active material layer. 2 . The positive electrode for a lithium-sulfur secondary battery according to claim 1 , wherein the gravure pattern has a width of 1 μm to 100 μm. 3 . The positive electrode for a lithium-sulfur secondary battery according to claim 1 , wherein a depth of the intaglio pattern is 30% to 99% based on a thickness of the positive electrode active material layer. 4 . The positive electrode for a lithium-sulfur secondary battery according to claim 1 , wherein the intaglio pattern has a shape of a plurality of straight lines or dotted lines that are horizontal or vertical to each other. 5 . The positive electrode for a lithium-sulfur secondary battery according to claim 1 , wherein the intaglio pattern has a shape of a plurality of dots formed in a manner of being spaced apart from each other. 6 . The positive electrode for a lithium-sulfur secondary battery according to claim 1 , wherein the intaglio pattern is located within 200 μm based on a predetermined point located on the surface of the positive electrode active material layer. 7 . The positive electrode for a lithium-sulfur secondary battery according to claim 1 , wherein the positive electrode active material layer contains 60 to 95 parts by weight of the positive electrode active material based on 100 parts by weight of the positive electrode active material layer. 8 . The positive electrode for a lithium-sulfur secondary battery according to claim 7 , wherein the positive electrode active material comprises a sulfur-carbon composite material, and the sulfur-carbon composite material contains 60 to 90 parts by weight of sulfur based on 100 parts by weight of the sulfur-carbon composite material.

9. A method for manufacturing a positive electrode for a lithium-sulfur secondary battery according to claim 1, the method comprising the following steps: (1) forming a positive electrode active material layer before rolling by applying a slurry for forming a positive electrode active material onto a current collector; (2) forming a rolled positive electrode active material layer by rolling the positive electrode active material layer before rolling; as well as (3) forming a positive electrode active material layer having an intaglio pattern, wherein the intaglio pattern is formed by irradiating a laser on the surface of the roll-pressed positive electrode active material layer, The positive electrode active material layer after rolling has a porosity of 50% to 65%, The spacing between the gravure patterns is less than 500 μm, The positive electrode active material layer maintains the same porosity before and after patterning.

10. The method according to claim 9, wherein the rolling in step (2) is performed using a rolling process. 11 . The method according to claim 9 , wherein the thickness of the positive electrode active material layer after rolling in step (2) is 70% to 90% of the thickness of the positive electrode active material layer before rolling in step (1).

12. The method according to claim 9, wherein the laser in step (3) has a wavelength range of 300 nm to 2000 nm and a frequency of 10 kHz to 1000 kHz.

13. The method according to claim 9, wherein the loading loss rate of the positive electrode active material caused by step (3) is 2.5% to 20%. 14 . A lithium-sulfur secondary battery, comprising the positive electrode according to claim 1 .

Citation Information

Patent Citations

  • Electrode for secondary battery and method for manufacturing the same

    KR1020150082958A

  • Masking the edge region of the donor substrate during the ion implantation step.

    KR1020190117573A

  • Method for manufacturing reflective mask blanks, reflective masks, and semiconductor devices

    KR1020190117755A

  • Pressing process of creating a patterned surface on battery electrodes

    CN108963181A

  • Electrolyte and lithium-sulfur battery using same, and preparation method and application of lithium-sulfur battery

    CN109346770A